Analisis Dan Perancangan Sistem Informasi Inventaris Barang Pada Kantor Kecamatan Tebo Ilir - Amin, Sagi Al; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2021)
Existing technology is developing so rapidly. it is supported by adequate and quality natural and human resources. various information and management of agency management at this time is very supportive to be developed into a system that relies on technological progress. one of them is information technology and data processing. at this time the form of information and data can be made in accordance with what we want, and many opportunities that can be utilized to develop it. the purpose of this study is to analyze the design of vehicle inventory information systems, equipment inventory, receipt of goods, data on damaged goods, data on improper use of goods, data on service goods and making reports with the methodology used is system modeling using UML (Unified Modeling Language) consisting from use case diagrams, Activity Diagrams and Class Diagrams, with plans limited to prototypes. This research resulted in a prototype of an inventory information system that can manage computerized inventory data and can present reports needed every day or every month.